Local Government Coordination in Flood Mitigation Policy: Insights from Cirebon - Hery Nariyah; Darwanto Darwanto; Ikhsan Nendi; Muhammad Asril Maulana; Fitri Maghdalena (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
Flood mitigation in Indonesian coastal cities depends not only on infrastructure but on how local government institutions coordinate across sectors and administrative levels. Cirebon, a dual river-and-tidal flood-prone city on the north coast of West Java, exemplifies coordination challenges of Indonesia's decentralised disaster governance, where the city, regency, technical agencies, and community actors operate with overlapping mandates. This study examines how local government coordination is structured, practised, and constrained in flood mitigation policy. Data were collected through interviews with 22 key informants from eight institutions, two focus group discussions, field observation, and document analysis, analysed using the Miles and Huberman interactive model with inter-coder reliability verification. Findings show coordination operates through three overlapping mechanisms: formal command-line coordination led by the Regional Disaster Management Agency (BPBD), semi-formal multi-stakeholder forums, and informal digital communication channels. Effectiveness is constrained by fragmented budget authority, the city-regency administrative split, weak SOP enforcement, and limited real-time data sharing, while community-based early warning groups and sustained leadership commitment act as key enablers. The study offers context-specific evidence for strengthening cross-sector flood governance in mid-sized Indonesian coastal cities.